PRODUCTION OF LARGE STEEL THIN-SECTION CASTINGS FOR CARGO RAILWAY CARS USING MODEM FOUNDRY TECHNOLOGIES - A. P. Melnikov; D. М. Kukuj; A. V. Cherapovich (Литьë и металлургия, 2008)
It is shown that at production of big steel castings “Beam ” and ‘'Frame ” under new technology labor intensiveness is reduced, eliminating defect by hot cracks.